2021
DOI: 10.3390/idr13040082
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Serology Testing in an Asymptomatic, At-Risk Population: Methods, Results, Pitfalls

Abstract: The primary aim of this study was to determine the seroprevalence of SARS-CoV-2 antibodies in a population of pediatric healthcare workers (HCWs). This study was conducted 14 May–13 July 2020. Study participants included pediatric HCWs at a pediatric hospital with either direct patient contact or close proximity to patient-care areas. SARS-CoV-2 antibodies were assessed via the Wytcote Superbio SARS-CoV-2 IgM/IgG Antibody Fast Detection Kit and the Abbott Architect SARS-CoV-2 IgG assay. Participants underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…There are a potential myriad of reasons baseline anxiety may have increased between phase 1 and phase 2, including differing study populations and rising case counts in the surrounding areas with a community prevalence in phase 1 of 99.5 per 100,000 compared to 458 per 100,000 during phase 2. 25,26 This study also demonstrated that from baseline to testing day 3, anxiety decreased in participants that tested positive or negative. After testing day 3, reported anxiety in those with positive results increased back towards baseline anxiety levels whereas decreased anxiety levels in the negative group were maintained through testing day 7.…”
Section: Discussionmentioning
confidence: 63%
“…There are a potential myriad of reasons baseline anxiety may have increased between phase 1 and phase 2, including differing study populations and rising case counts in the surrounding areas with a community prevalence in phase 1 of 99.5 per 100,000 compared to 458 per 100,000 during phase 2. 25,26 This study also demonstrated that from baseline to testing day 3, anxiety decreased in participants that tested positive or negative. After testing day 3, reported anxiety in those with positive results increased back towards baseline anxiety levels whereas decreased anxiety levels in the negative group were maintained through testing day 7.…”
Section: Discussionmentioning
confidence: 63%
“…Although those in the PICU also reported higher levels of baseline anxiety, this is somewhat difficult to interpret as those working in the PICU only participated in phase 2, which was itself associated with higher levels of baseline anxiety regarding the COVID-19 pandemic. There are a potential myriad of reasons why baseline anxiety may have increased between phase 1 and phase 2, including differing study populations and rising case counts in the surrounding areas, with a community prevalence in phase 1 of 99.5 per 100,000 compared to 458 per 100,000 during phase 2 [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%